Large Colonic Lipoma, Presentation and Treatment: Case Reports and Literature Review - Ahmed, Salwa Sid; Ali, Syed Muhammad; Shahid, Fakhar; Abunada, Mohamed Hosni; Parvaiz, Amjad (International Journal of Innovative Research in Medical Science, 2022)
Colonic lipomas are uncommon tumors that may remain asymptomatic and seen incidentally on endoscopy, surgery, or autopsy. They can cause constipation, bleeding that may lead to anemia, and acute abdominal pain due to intussusception if larger than five centimeters, particularly when pedunculated. Colonoscopy can reveal a protruding luminal mass, whereas a Computed Tomography (CT) can precisely localize, indicate the nature, and characterize the composition. Removal by endoscopy in smaller and surgical resection remains the treatment of choice for larger lesions by open laparotomy or laparoscopy. We describe a case series of three patients who underwent laparoscopic resection of the colon for symptomatic large lipomas in our hospital.